2014
DOI: 10.1007/s10876-014-0821-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures and Luminescent Properties of 3D Copper(I) 1,2,4-Triazolates Containing Cubic Cu4X4 Clusters (X = Cl, Br)

Abstract: Reactions of 3,5-disubstituted-1,2,4-triazoles with CuX 2 (X = Cl, Br) under hydrothermal condition yield six copper(I) triazolates: [Cu 2 (3,5-n Bu 2 tz)Cl] n (1), [Cu 2 (3,5-i Bu 2 tz)Cl] n (2), {Cu 2 (3,5-(C 6 H 11 ) 2 tz)Cl} n (3), [Cu 2 (3,5-s Bu 2 tz)Br] n (4), {Cu 2 (3,5-(C 6 H 11 ) 2 tz)Br} n (5), {Cu 2 [3,5-(p-Tol) 2 tz]Br} n (6), where 3,5-n Bu 2 tz, 3,5-i Bu 2 tz, 3,5-s Bu 2 tz are 3,5-dibutyl-1,2,4-triazolate, 3,5-dii-butyl-1,2,4-triazolate, 3,5-dis-butyl-1,2,4-triazolate; 3,5-(C 6 H 11 ) 2 tz is 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[13] At the same time, analogous tetranuclearc lusters have been reported,w hich are formally built up by combining two Cu 2 I 2 subunits. [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] At this point, it is important to mention that the very first OLED based on Cu I contained the tetranuclear complexC u 4 (CCph) 4 L 2 (L = 1,8-bis(diphenylphosphino)-3,6-dioxaoctane). [29] Lu et al reported on ah ighly luminescent tetranuclear system with aC u 4 Cl 4 core and 2-(bis(2-methyl-phenyl)phosphino)-6-methylpyridine as bridging ligand,s howinga combination of TADF and fast phosphorescence at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[13] At the same time, analogous tetranuclearc lusters have been reported,w hich are formally built up by combining two Cu 2 I 2 subunits. [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] At this point, it is important to mention that the very first OLED based on Cu I contained the tetranuclear complexC u 4 (CCph) 4 L 2 (L = 1,8-bis(diphenylphosphino)-3,6-dioxaoctane). [29] Lu et al reported on ah ighly luminescent tetranuclear system with aC u 4 Cl 4 core and 2-(bis(2-methyl-phenyl)phosphino)-6-methylpyridine as bridging ligand,s howinga combination of TADF and fast phosphorescence at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of complexes are binuclear with a rhomboidal shape, which acts as a building block for higher nuclearity molecular and for polymeric complexes . Conversely, for complexes containing four copper nuclei, several distorted cubane type, stair step and planar parallelogram structures with varying Cu ⋅⋅⋅ Cu interactions have been reported, as the topological arrangement of four atoms in space changes with the nature of ancillary ligand and halide ion. This structural diversity of copper(I) complexes continues to grow, as new tailor‐made ligands with unique steric and electronic factors are invented in conjunction with different sizes of halide atoms and reaction conditions…”
Section: Introductionmentioning
confidence: 99%